“O Censo é a Infraestrutura Informacional do País”: O Censo de 2020 e as Controvérsias Tecnopolíticas de sua Implementação - Moisés Kopper (Confins)
This article explores the techno-political controversies related to the implementation of the 2020 census in Brazil. Through interviews and documentary research, I have mapped the techno-moral debates and the socio-technical transformations of two of its devices: the questionnaire and the budget. This approach allowed to highlight the emergence of a form of activism carried by the mobilization of experts. The text concludes by interpreting the census as an informational infrastructure that inscribes, imagines and stabilizes ideals for the future through numbers.